2020
DOI: 10.1002/ets2.12288
|View full text |Cite
|
Sign up to set email alerts
|

The Redesigned TOEIC Bridge® Tests: Relations to Test‐Taker Perceptions of Proficiency in English

Abstract: The redesigned four‐skills TOEIC Bridge® tests were designed to measure the listening, reading, speaking, and writing proficiency of beginning to low–intermediate English learners in the context of everyday life. In this paper, I describe two studies that were conducted to investigate claims about the meaningfulness of redesigned TOEIC Bridge test scores by comparing them to self‐assessments of listening, reading, speaking, and writing proficiency. In Study 1, test takers who participated in the redesigned TOE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…For language skills that are not directly observable, such as listening and reading comprehension, language learners may be in a unique position to have insight into their competencies. Schmidgall (2020) conducted two research studies in which TOEIC Bridge test scores were compared to test takers' self‐evaluations of their ability to complete everyday listening, reading, speaking, or writing tasks in English and found that TOEIC Bridge Listening, Reading, Speaking, and Writing test scores were moderately correlated with self‐assessments ( r = .55, .54, .51, and .46, respectively). These results compare favorably with the results of similar studies of the relationship between self‐assessments and criterion measures; in a meta‐analysis that included 67 studies, Li and Zhang (2021) found that the overall correlation between self‐assessment and language performance was .466.…”
Section: Claim 3: Score Interpretations Are Meaningful Impartial Generalizable and Relevantmentioning
confidence: 99%
“…For language skills that are not directly observable, such as listening and reading comprehension, language learners may be in a unique position to have insight into their competencies. Schmidgall (2020) conducted two research studies in which TOEIC Bridge test scores were compared to test takers' self‐evaluations of their ability to complete everyday listening, reading, speaking, or writing tasks in English and found that TOEIC Bridge Listening, Reading, Speaking, and Writing test scores were moderately correlated with self‐assessments ( r = .55, .54, .51, and .46, respectively). These results compare favorably with the results of similar studies of the relationship between self‐assessments and criterion measures; in a meta‐analysis that included 67 studies, Li and Zhang (2021) found that the overall correlation between self‐assessment and language performance was .466.…”
Section: Claim 3: Score Interpretations Are Meaningful Impartial Generalizable and Relevantmentioning
confidence: 99%